Frequency of Multiple Paternity in the Spiny Dogfish Squalus acanthias in the Western North Atlantic - Veríssimo, Ana; Grubbs, Dean; McDowell, Jan; Musick, John; Portnoy, David (Journal of Heredity, 2010)
Multiple paternity (MP) has been shown to be widespread in elasmobranch fishes although its prevalence and the number of sires per litter vary considerably among species. In the squaloid shark Squalus acanthias , MP has been reported, but whether it is a common feature of the species’ reproductive strategy is unknown. In this study, we determined the frequency of MP in 29 litters of S. acanthias sampled from the lower Chesapeake Bay and coastal Virginia waters, using 7 highly polymorphic nuclear DNA microsatellite loci. Only 5 litters (17% of the total) were genetically polyandrous, with at least 2 sires per litter. Litter size increased with female size but was similar between polyandrous and monandrous females.